Communicating for success - Kossen, Christopher , 1963-; Kiernan, Eleanor F.; Lawrence, Jill E. (Pearson Australia, 2013)
Communication is central to being human and the way we experience life. The aim of this book is to assist students in further developing and refining communication skills in an effort to optimise performance across a range of pursuits, both academic and otherwise. Key performance skills dealt with in this book relate to academic performance, professional performance and competencies for dealing with people, as well as cultivating productive relationships. The book has a strong focus on academic skills with chapters covering university culture and transition skills, academic writing including research and referencing, and communication theory. Additionally, it examines skills used in university studies which are also applicable to personal and professional contexts, including areas relating to digital, oral and nonverbal communication as well as issues around persuasion, argument and ethics.